Analysis of the characteristics of the ejector mode of the pulse detonation propulsion system of the combined acceleration cycle - Olena Zolotko; Oleksandr Zolotko; Oleksandr Aksonov; Vitalii Stoliarchuk; Oleksandr Cherniavskyi (Авіаційно-космічна техніка та технологія)
The subjects of this article are processes in the chamber of the pulse detonation propulsion system of the combined acceleration cycle (PSCA). The goal is to identify the most significant factors and study their influence on the defining characteristics of the ejector mode of operation of the pulse detonation PSCA. The task: to consider promising concepts of multi-mode engines and to investigate the influence of the mode parameters and design factors on the coefficient of increase of the thrust-specific impulse and the coefficient of increase of the thrust of the ejector. Methods of problem solving: computational analytical and experimental approaches. The following results were obtained. An analysis of the concept of multi-mode engines in transatmospheric aircraft was performed. The most famous of them include: two-mode direct-jet engine (ramjet-scramjet engine); rocket-based combined cycle (RBCC) engine; hybrid air-breathing rocket engine (Synergetic Air-Breathing Rocket Engine, SABRE). The propulsion system of the combined cycle of acceleration combines the main advantages of air-jet and rocket engines and can provide direct access to outer space (the concept of single stage to orbit, SSTO). A new stage in the development of PSCA is associated with the use of detonation mode combustion. During detonation, the pressure in the combustion chamber of the engine increases, which allows the pump to be excluded from the propulsion system. The following acceleration cycles are integrated into the pulse-detonation propulsion system: rocket-detonation; rocket-detonation with ejector thrust enhancement; jet-detonation with a direct or oblique detonation wave. In a promising engine for transatmospheric aircraft (Sodramjet), a stable and fixed oblique detonation wave is created under hypersonic flight conditions. Conclusions. It was established that with a certain combination of the studied factors, the coefficient of increase of the thrust-specific impulse reaches its maximum value. The dependence of the ejector thrust enhancement coefficient ΦP is determined by the flight conditions. The mode of self-similarity (independence) of ΦP from the flight height occurs at a speed of M = 5 and altitudes greater than 8 km. It is proposed to use a turbopump supply system without a gas generator to supply the rocket fuel components to the detonation combustion chamber. The influence of the initial pressure in the detonation chamber on the coefficient of increase of the thrust of the ejector ΦP and the magnitude of the specific impulse was investigated by computational fluid dynamics using the TVD scheme. The environmental advantages of using the detonation cycle of combustion in rocket and space technology are analyzed.